THE TRANSFORMATION OF ISLAMIC EDUCATION THROUGH TECHNOLOGY INTEGRATION IN THE DIGITAL ERA - St. Wardah Hanafie Das; Muhammad Zaid; Muminayah; Rahmaniah (Journal International Inspire Education Technology, 2025)
The rapid advancement of technology in the digital era has fundamentally transformed various aspects of human life, particularly in the way information is created, stored, and disseminated. In the context of Islamic education, this digital transformation presents both significant opportunities and complex challenges. This study explores the urgency of adapting Islamic education to technological progress to ensure its relevance for "digital native" generations. The findings indicate that digital technology serves as a powerful tool to expand accessibility to Islamic teachings through e-learning, mobile applications, and online platforms, while also fostering 21st-century skills such as critical thinking and digital literacy. However, this shift necessitates rigorous oversight to combat the spread of inaccurate or distorted content that may conflict with Islamic principles. This research provides a conceptual framework for integrating technology into Islamic Religious Education (PAI) and identifies strategic solutions to overcome the barriers of digital transformation, aiming to produce a generation that is both spiritually grounded and technologically proficient.